2017
DOI: 10.1101/237644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A simple bioreactor-based method to generate kidney organoids from pluripotent stem cells

Abstract: SummaryKidney organoids generated from human pluripotent stem cells have the potential to revolutionize how kidney development and injury are studied. Current protocols are technically complex and suffer from poor reproducibility and high reagent costs restricting scalability. To overcome these issues, we have established a simple, inexpensive and robust method to grow kidney organoids in bulk from human induced pluripotent stem cells. Our organoids develop tubular structures by day (d) 8 and show optimal tiss… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…All work was carried out with the approval of Human Participants Ethics Committees (UAHPEC 8712 and HDEC 17/NTA/204) and biosafety. iPSC maintenance and kidney organoid generation were performed as described (13). All experiments were performed using organoids generated from the MANZ-2 iPSC line (13).…”
Section: Ipsc Maintenance and Organoid Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…All work was carried out with the approval of Human Participants Ethics Committees (UAHPEC 8712 and HDEC 17/NTA/204) and biosafety. iPSC maintenance and kidney organoid generation were performed as described (13). All experiments were performed using organoids generated from the MANZ-2 iPSC line (13).…”
Section: Ipsc Maintenance and Organoid Generationmentioning
confidence: 99%
“…We have developed a novel kidney organoid protocol that uses a simple, cost-effective method to generate large numbers of organoids, making it ideally suited for injury modeling and drug development (13). Here, we used these kidney organoids to analyze the effects and specificity of cisplatin-induced AKI.…”
Section: Introductionmentioning
confidence: 99%
“…Technologies to generate kidney organoids from human induced pluripotent stem cells (iPSC) (Cruz et al, 2017a;Forbes et al, 2018a;Freedman et al, 2015;Morizane and Bonventre, 2017a;Morizane et al, 2015;Przepiorski et al, 2018;Taguchi and Nishinakamura, 2017;Taguchi et al, 2014;Takasato et al, 2015aTakasato et al, , 2016aTanigawa et al, 2018a) provide a promising avenue to further help advance our understanding of disease mechanisms and expedite therapeutic development.…”
Section: Introductionmentioning
confidence: 99%
“…Takasato et al [5,6] developed a relatively simple protocol, while the method of Morizane et al [7] required a shorter culture time. Recently, Przepiorski et al [8] reported a simple and cost-effective protocol using a bioreactor. These protocols share certain features but also have some distinct aspects.…”
Section: Generation Of Kidney Organoids From Induced Pluripotent Stemmentioning
confidence: 99%
“…These protocols share certain features but also have some distinct aspects. Although the similarities and differences between the nephron progenitors and nephrons induced by these different protocols need to be determined, the induced proximal renal tubules have been shown to carry out some functions, including reabsorption of low-molecular-weight dextran [6,8] and selective cell death in response to nephrotoxic drugs [6,7].…”
Section: Generation Of Kidney Organoids From Induced Pluripotent Stemmentioning
confidence: 99%